Quantitative thyroid scintigraphy for the differentiation of Graves’ disease and hyperthyroid autoimmune thyroiditis - Sahlmann, C. O.; Siefker, U.; Lehmann, K.; Harms, E.; Conrad, M.; Meller, J. (Nuklearmedizin - NuclearMedicine, 2004)
Aim: The TCTUs (global 99mTc-pertechnetate thyroid uptake under suppression) can be used as an estimate of the iodine clearance of non-TSH regulated tissue. High TCTUs levels are characteristic for Graves’ disease (GD). Decreased uptake has been described in autoimmune thyroiditis (AIT). However, systematically investigated data in a larger series of AIT-patients with subclinical or overt hyperthyroidism are not published so far. The purpose of this study is the evaluation of the TCTUs in the differentiation between AIT and GD in patients with hyperthyroidism. Methods: We determined the TCTUs in 59 patients with untreated hyperthyroid GD and in 51 patients with AIT who had subclinical or manifest hyperthyroidism without medication. Patients with GD were characterized by the presence of hyperthyroidism, decreased echogenicity of the thyroid, elevation of TSH-receptor autoantibodies (TRAb). AIT was defined by a decreased echogenicity of the thyroid, absence of elevated TSH-receptor autoantibodies (TRAb), autoantibodies against the thyroid peroxidase (anti-TPO) and spontaneous remission or development of subclinical hypothyroidism within 3 months. Results: Thyroid volumes of patients with AIT were significantly lower than those of patients with GD (p <0.05). TRAb levels were significantly higher in GD-patients (median: 19.5 U/ml; range: 15.3-35 U/ml) than in AIT-patients (median: 1.3 U/ml; range: 0-4.1 U/ml). 73% (38/59) of patients with GD had elevated anti-TPO levels. In these patients anti-TPO levels (median: 768 U/l; range: 83-6397 U/l) were not significantly different from anti-TPO levels of patients with AIT (median: 834 U/l; range: 107-8675 U/l; p = 0.17). TCTUs values of patients with AIT were significantly lower (p <0.05; median: 0.9%; range: 0.1-3.2%) than those of patients with GD (median: 5.7%; range: 1.9-28.3%). Conclusion: In our patients quantitative thyroid scintigraphy with 99mTcO4- offered rapid and reliable differentiation between hyperthyroid GD and AIT.
Keywords: Graves’ diseasne; autoimmune thyroiditis; TSH-receptor antibodies; pertechnetate; thyroid scintigraphy; sodium/iodide symporter